2015
DOI: 10.1101/gr.195164.115
|View full text |Cite
|
Sign up to set email alerts
|

Nascent RNA folding mitigates transcription-associated mutagenesis

Abstract: Transcription is mutagenic, in part because the R-loop formed by the binding of the nascent RNA with its DNA template exposes the nontemplate DNA strand to mutagens and primes unscheduled error-prone DNA synthesis. We hypothesize that strong folding of nascent RNA weakens R-loops and hence decreases mutagenesis. By a yeast forward mutation assay, we show that strengthening RNA folding and reducing R-loop formation by synonymous changes in a reporter gene can lower mutation rate by >80%. This effect is diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 58 publications
3
31
0
Order By: Relevance
“…4A). We kept features that may influence local mutation rate such as GC content, codon usage, and predicted local mRNA structure largely unchanged (Table S4) [13,17,25]. The expression levels of URA3 in these variants are also identical ( Fig.…”
Section: Genetic Manipulation Of Dna Curvature Affects Mutation Ratementioning
confidence: 99%
See 1 more Smart Citation
“…4A). We kept features that may influence local mutation rate such as GC content, codon usage, and predicted local mRNA structure largely unchanged (Table S4) [13,17,25]. The expression levels of URA3 in these variants are also identical ( Fig.…”
Section: Genetic Manipulation Of Dna Curvature Affects Mutation Ratementioning
confidence: 99%
“…A large number of trans factors influencing mutation rate have been identified [1], such as chromatin remodelers, histone-modifying enzymes, and other DNA binding proteins [2][3][4]. In addition, replication timing [5][6][7][8][9] and transcription rate [10][11][12][13][14] also affect mutation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide analysis in yeast has confirmed an enrichment of R-loops at highly transcribed regions [41-43]. Consistent with active transcription exposing the NTS as ssDNA, alterations in primary sequence that increase nascent RNA folding, which is predicted to reduce R-loop formation, mitigate TAM [44]. It should be noted, however, that direct evidence of an NTS-bias in the accumulation of endogenous DNA damage has not been reported in yeast.…”
Section: Transcription As a Source Of Genetic Instabilitymentioning
confidence: 99%
“…Generally, transcription is mutagenic and DNA damage is partly due to the R‐loop formed through the binding of the nascent RNA with its DNA template exposing the DNA nontemplate strand to mutagens and to primers that induce unscheduled error‐prone DNA synthesis . A recent study revealed that nascent RNA folding can mitigate transcription‐associated mutagenesis (Figure (b)) . The authors illustrated that heightening RNA folding and reducing R‐loop formation by synonymous changes in a reporter gene can lower the mutation rate immensely.…”
Section: Functions Of Rna Conformational Transitionsmentioning
confidence: 99%
“…21,49 A recent study revealed that nascent RNA folding can mitigate transcription-associated mutagenesis (Figure 2(b)). 50 The authors illustrated that heightening RNA folding and reducing R-loop formation by synonymous changes in a reporter gene can lower the mutation rate immensely. Over-expression of the gene RNase H1 can degrade the RNA in a DNA-RNA hybrid and decrease the effect, implying that it is R-loop dependent.…”
Section: Transcription Activation and Termination And Mutagenesismentioning
confidence: 99%